Correlates of body mass index among primary school children in Ho Chi Minh City, Vietnam. (April 2020) - Pham, N.K.; Sepehri, A.; Le, T.M.; Tran, V.T.
Abstract: Objectives: To document the prevalence of overweight and obesity and examine associated risk factors. Study design: A cross-sectional survey was conducted in 16 primary public schools in eight districts of Ho Chi Minh City in 2016. A multistage clustering sampling method was used to collect a sample of 1806 pupils attending the first, second, and third grades (7–9 years). Methods: Age- and sex-adjusted body mass index (BMI) status was defined using International Obesity Taskforce cut-offs. Ordered probit regression models were used to assess the association between child BMI and its socio-economic and demographic risk factors. The model was estimated separately for boys and girls to assess the extent to which the socio-economic gradients in BMI vary by gender. Results: The prevalence of obesity among boys was twice the rate for girls (24.7 vs 12.3%). The prevalence of overweight and obesity were also higher among pupils attending schools located in urban districts than in semi-rural districts. Gender, household wealth, the frequency of having breakfast at home, parental body weight, and school location were strong predictors of child BMI status. The protective effect of having breakfast more frequently at home against the risk of overweight/obesity was more pronounced in girls than in boys. Father's body weight and child BMI were more strongly associated with boys from poorer households than boys from wealthier households, while the differences were not significant for girls. Conclusions: The high prevalence of childhood overweight and obesity indicates an urgent need for more gender-specific, effective intervention, and prevention programs. Highlights: The prevalence of obesity among boys was twice the rate for girls (24.7 vs 12.3%). The prevalence of overweight was significantly greater in children from the wealthy than less wealthy households. School location was a strong predictor of BMI only for children from the less wealthy households. Father's body weight and child BMI were more strongly associated in boys from poorer households than from rich households.